Effect of H2O on the volatilization characteristics of arsenic during isothermal O2/CO2 combustion - Zou, Chan; Wang, Chunbo; Liu, Huimin; Chen, Liang; Anthony, Edward J. (Elsevier, 2019)
The effect of H2O on the volatilization behavior of arsenic in coal was studied under O2/CO2 combustion conditions at 800–1300 ºC, which covers the effective range of coal combustion temperatures appropriate for conventional coal combustion technologies. By controlling the combustion time of the coal, the volatilization percentage and rate of As emissions versus time were obtained. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses were used to study the evolution of minerals with and without H2O under O2/CO2 combustion conditions. The effect of CO2 on As volatilization was first investigated and it was found that increasing CO2 concentrations inhibits the volatilization of As, with this effect decreasing with increasing temperature. When a fraction of the CO2 was replaced with H2O, the volatilization of As increased, but the positive effect of H2O also decreased with increasing temperature. The volatilization percentage of As with 30% H2O was 6.1% higher than that without H2O at 800 ºC, while it was only 2.7% higher at 1300 ºC. When the concentration of H2O increased from 0 to 30%, the peak value of the As volatilization rate increased and the time needed to reach the peak value decreased. The volatilization characteristics of As for three coals were very similar, which demonstrates that the effect of H2O was not limited to only one specific coal.
Keywords: O2/CO2 combustion; Arsenic; Volatilization characteristics; H2O